Complementary spaces in marine littoral exploitation? A comparative study of rock shelter and shell middens occupations from the lower basin of the Deseado River, Argentine Patagonia - Ambrustolo, Pablo (The Journal of Island and Coastal Archaeology)
The archaeological record of the Province of Santa Cruz’s north Atlantic coast in Argentine Patagonia is represented mainly by middens. These shell middens are made up of the calcareous exoskeletons of mollusks, as well as skeletal remains of vertebrate fauna, lithic artifacts, and carbonized plant remains, intermixed with a varying quantity of sedimentary soil. Recently, along the Lower Basin of the Deseado River, outcrops have been identified that would have functioned in the past as rock shelters for hunter-gatherers who occupied the area during the Middle and Late Holocene. With the aim of expanding our knowledge concerning the dynamics of use of coastal spaces, we began a stratigraphic study of the shell middens and rock shelters. Here, we present a comparative analysis of the occupation characteristics registered at both types of sites and their possible structuring in terms of mobility and functionality. Rock shelters would have functioned primarily as contexts for short-term activities related to the processing and consumption of fauna, mainly terrestrial and to a lesser extent marine fauna. These probably structured seasonal mobility strategies that linked coastal shell middens, defined as multiple activity contexts, with hinterland areas that might have been related to the specific pursuit of other activities. Fil: Ambrustolo, Pablo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina